2015
DOI: 10.1007/s00216-015-9173-5
|View full text |Cite
|
Sign up to set email alerts
|

Biased cyclical electrical field-flow fractionation for separation of submicron particles

Abstract: The potential of biased cyclical electrical field flow fractionation (BCyElFFF), which applies the positive cycle voltage longer than the negative cycle voltage, for characterization of submicron particles, was investigated. Parameters affecting separation and retention such as voltage, frequency, and duty cycle were examined. The results suggest that the separation mechanism in BCyElFFF in many cases is more related to the size of particles, as is the case with normal ElFFF, in the studied conditions, than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The ElFFF device used in the characterization tests was the same device as described in previous publications from our group. , The ElFFF channel dimensions are 64 cm length, 178 μm height, and 2 cm breadth. A high-pressure isocratic pump (Agilent model 1260, Agilent, Inc., Santa Clara, CA) pumped the carrier liquid through the ElFFF system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ElFFF device used in the characterization tests was the same device as described in previous publications from our group. , The ElFFF channel dimensions are 64 cm length, 178 μm height, and 2 cm breadth. A high-pressure isocratic pump (Agilent model 1260, Agilent, Inc., Santa Clara, CA) pumped the carrier liquid through the ElFFF system.…”
Section: Methodsmentioning
confidence: 99%
“…ElFFF is a technique that separates particles based upon their electrophoretic mobility. This technique has been used for the characterization and separation of nanoparticles. , In this work, the ability of ElFFF to separate human plasma and U87 sEVs and mEVs was investigated, and their behavior was studied under different electrical conditions. Further, cyclical ElFFF (CyElFFF) theory was applied to calculate the electrophoretic mobility of U87 sEVs using fractionation data.…”
mentioning
confidence: 99%
“…One difficulty in using El-FFF for biological vesicle separation is that salt concentration within typical physiological vesicle buffers is high enough to reduce the strength of the effective electric field within the El-FFF channel. 28 Salt must be removed via buffer substitution if effective vesicle separation using El-FFF is to be achieved. Conceivably, buffer substitution may influence El-FFF dependent exosome subfractionation.…”
mentioning
confidence: 99%
“…251−254 However, separation performance in constant voltage operation was limited due to the induced polarized layer on the surface of electrodes which weakened the effective electric field. 242,249,255,256 To increase the effective electric field, a pulse reversing technique was introduced as an alternative approach to discharge the polarized layer, thereby improving separation performance. 242,249,257−259 Using the pulsed voltage strategy, it is possible to optimize the retention behavior of nanoparticles via parameters such as pulse frequency, duty cycle, and waveform.…”
Section: Label-free Microfluidic Methods For Exosome Isolationmentioning
confidence: 99%
“…They showed that appropriate voltage waveforms suppressed the high diffusion rate of gold nanoparticles with sizes <50 nm and fractionated them with the highest resolution at a duty cycle of 75%. 242,257 Although electrical-FFF exhibits a significant capability to separate nanoparticles, it has rarely been tested for EV isolation. EVs are known to possess negative surface charge, thereby electrical-FFF could serve to gently separate EV subtypes based upon their electrophoretic mobility.…”
Section: Label-free Microfluidic Methods For Exosome Isolationmentioning
confidence: 99%